Doratask: The Effect of Runway Occupation Time on Optimizing Runway Capacity at Nop Goliat Dekai Airport - Ramadani, Rizki Agung; Hati, Berliyana Kesuma (Syntax Literate, 2025)
Nop Goliat Dekai Airport experienced an increase of 18.8 percent per year for passengers, 27.9 percent for cargo, and 19.4 percent of airport capacity both in terms of land and air. Due to the increasing number of aircraft movements, airport management is evaluating the value of runway capacity to improve service and comfort for airport customers. The aim of this research is to see how runway occupancy time and runway capacity influence the optimization of runway use. By using the DORATASK approach, this research aims to estimate the impact of runway occupancy time and runway capacity on air traffic services. The values for occupancy time and available runway capacity are still below the maximum values and have no effect on air traffic services, the study found. Runway 25 has an average Runway Occupancy Time (MROT) of 122.35 seconds, while runway 07 has a MROT of 115.23 seconds. Based on calculations, the Declared Runway Capacity (DCR) is 14 movements per hour, but currently the runway is only used 80% or 11 movements per hour at the busiest hours. This data shows that the runway capacity at Nop Goliat Dekai Airport is still in accordance with its performance.